Education and Artificial Intelligence: An Analysis Based on Teachers' Opinions. - Yurtseven, Ramazan; Baysal, Emine Akkaş; Ocak, Gürbüz (Pertanika Journal of Social Sciences & Humanities, 2025)
Artificial intelligence has become increasingly present in people's lives, significantly impacting various fields, including education. The impact of artificial intelligence brings the opportunity to transform and adapt how the teaching-learning process is carried out. In this context, the research aimed to determine teachers' opinions regarding using artificial intelligence in education. The phenomenological pattern, one of the qualitative research methods, was used in the study. Criterion sampling, one of the purposeful sampling methods, was used. Research data was collected from 40 teachers working in different branches using a semi-structured interview form. The data obtained was analyzed using content analysis. The research findings underscore the potential benefits of integrating artificial intelligence into education, offering various opportunities for enhancing the teaching and learning experience. While acknowledging the efficiency and benefits highlighted by some educators, it is imperative to exercise caution and implement artificial intelligence within ethical boundaries. Within the school environment, artificial intelligence is poised to revolutionize physical, managerial, and technological aspects, alleviating administrative burdens and facilitating smoother operations. In the teaching process, artificial intelligence holds promise for creating enriched learning environments, promoting active student engagement, and optimizing time utilization for educators. Moreover, in evaluation, artificial intelligence stands to enhance objectivity in assessments. Artificial intelligence presents opportunities for students to save time, foster individual growth, and streamline learning experiences, ultimately facilitating their academic journey and professional development.